Curative Effect of Prebiotics/Probiotics-Assisted Ketogenic Diet on Children with Refractory Epilepsy - Lingying Su; Sai Li; Bo Sun (Emergency Medicine International)
Objective. The aim is to study the curative effect of prebiotics/probiotics-assisted ketogenic diet (KD) on children with refractory epilepsy. Methods. A retrospective analysis was performed on the clinical data of 80 children with refractory epilepsy treated in the hospital between December 2018 and December 2020. According to different treatment methods, they were divided into the KD group (36 cases, KD) and combination group (44 cases, prebiotics/probiotics assisted KD). All were followed up for 1 year. The curative effect, electroencephalogram findings, levels of neurotransmitters, quality of life scores, cognitive function (verbal intelligence quotient (VIQ), performance intelligence quotient (PIQ)), and incidence of adverse reactions were compared between the two groups. Results. At the last follow-up, the effective rate of the combination group was higher than that of the KD group (95.45% vs 80.56%) (P<0.05). After 1 year of treatment, video electroencephalogram findings in both groups were improved, and the response rate of the combination group was higher than that of the KD group (97.73% vs 83.33%) (P<0.05). After 1 year of treatment, levels of VIQ and PIQ in both groups were increased, which were higher in the combination group than the KD group (P<0.05). After 1 year of treatment, the level of 5-hydroxytryptamine (5-HT) in both groups was increased, which was higher in the combination group than the KD group (P<0.05). After 1 year of treatment, quality of life scores in both groups were increased, which was higher in the combination group than the KD group (P<0.05). The incidence of adverse reactions in the combination group was lower than that in the KD group (13.64% vs 36.11%) (P<0.05). Conclusion. The curative effect of prebiotics/probiotics-assisted KD is better on children with refractory epilepsy, which can effectively improve electroencephalogram and quality of life, increase neurotransmitters and cognitive levels, with good safety.